Comparative effectiveness from a single-arm trial and real-world data: alectinib versus ceritinib. (26th June 2018) - Davies, Jessica; Martinec, Michael; Delmar, Paul; Coudert, Mathieu; Bordogna, Walter; Golding, Sophie; Martina, Reynaldo; Crane, Gracy
Aim: To compare the overall survival of anaplastic lymphoma kinase -positive non-small-cell lung cancer patients who received alectinib with those who received ceritinib.Materials & methods: Two treatment arms (alectinib [n = 183] and ceritinib [n = 67]) were extracted from clinical trials and an electronic health record database, respectively. Propensity scores were applied to balance baseline characteristics. Kaplan–Meier and multivariate Cox regression were conducted.Results: After propensity score adjustment, baseline characteristics were balanced. Alectinib had a prolonged median overall survival (alectinib = 24.3 months and ceritinib = 15.6 months) and lower risk of death (hazard ratio: 0.65; 95% CI: 0.48–0.88).Conclusion: Alectinib was associated with prolonged overall survival versus ceritinib, which is consistent with efficacy evidence from clinical trials.